Discrete Coiled Coil Rotamers Form within the EGFRvIII Juxtamembrane Domain - Mozumdar, Deepto (Biochemistry, 2020)
Mutations in the epidermal growth factor receptor (EGFR) extracellular domain (ECD) are implicated in the development of glioblastoma multiforme (GBM), which is a highly aggressive form of brain cancer. Of particular interest to GBM is the EGFR variant known as EGFRvIII, which is distinguished by an in-frame deletion of exons 2–7, which encode ECD residues 6–273. Included within the deleted region is an autoinhibitory tether, whose absence, alongside unique disulfide interactions within the truncated ECD, supports assembly of a constitutively active asymmetric kinase dimer. Previous studies have shown that the binding of growth factors to the ECD of wild-type EGFR leads to the formation of two distinct coiled coil dimers in the cytoplasmic juxtamembrane (JM) segment, whose identities correlate with the downstream phenotype. One coiled coil contains leucine residues at the interhelix interface (EGF-type), whereas the other contains charged and polar side chains (TGF-α-type). It has been proposed that growth-factor-dependent structural changes in the ECD and adjacent transmembrane helix are transduced into distinct JM coiled coils. Here, we show that, in the absence of this growth-factor-induced signal, the JM of EGFRvIII adopts both EGF-type and TGF-α-type structures, providing direct evidence for this hypothesis. These studies confirm that the signals that define JM coiled coil identity begin within the ECD, and support a model in which growth-factor-induced conformational changes are transmitted from the ECD through the transmembrane helix to favor different coiled coil isomers within the JM.